Characterization of Clostridium perfringens Phage Endolysin PlyDolk21 - Suyoung Seo; Bokyung Son; Minsuk Kong (Antibiotics)
Background: Clostridium perfringens is a significant cause of food poisoning. Broad-spectrum antibiotics, commonly used to control C. perfringens, are becoming less effective due to the rise of antibiotic-resistant strains, necessitating alternative control strategies. Methods: A C. perfringens-infecting bacteriophage, Dolk21, and its endolysin, PlyDolk21, were isolated and characterized. The lytic activity of PlyDolk21 was assessed in comparison to its catalytic domain alone. Both PlyDolk21 and its cell wall binding domain (CBD) were evaluated in beef and milk for their antimicrobial activity and cell wall binding activity, respectively. Results: While phage Dolk21 was specific to certain C. perfringens strains, PlyDolk21 exhibited lytic activity against all C. perfringens strains tested. The full-length PlyDolk21 showed stronger lytic activity compared to its catalytic domain alone. PlyDolk21_CBD successfully bound to C. perfringens in vitro and in foods. Additionally, PlyDolk21 effectively reduced the viable cell counts of C. perfringens by 3-log in beef soup and milk samples. Conclusions: This study demonstrates that PlyDolk21 and its CBD hold potential as a biocontrol and detection agent targeting C. perfringens in various food matrices.